Sebelas Syarat Penentuan Lokasi Bendung Irigasi - - Soekrasno (Jurnal Irigasi, 2015)
Irrigation weir failure beside caused by inaccurate survey and investigation, not thoroughly design, poor construction implementation, poor operation and maintenance, but also caused by wrong irrigation weir site selection. Initial factor influencing irrigation weir performances is irrigation weir site selection. Weir would strong enough against external force, flood impulse, local scouring, river degradation in case of accurate weir site selection.This paper discusses eleven conditions in selecting irrigation weir site in order to obtain better weir performance, i.e. : topographic condition, geotechnical consideration, hydraulic, river regime, primary canal, weir site space, irrigation service area, catchment area, assesment, economic justification, stakeholder acceptance.Analyse of correlation between weir site selection during design and weir performance, to be combined with weir observation by means of directly site inspection and communication with weir operator has been carried out to justify those eleven conditions weir site selection.Generally weir site mis-selection caused by among others are: irrigation engineer’s incapability, less budget, time and manpower, and less professional engineer.